2019
DOI: 10.3389/fonc.2019.00776
|View full text |Cite
|
Sign up to set email alerts
|

LINC00957 Acted as Prognostic Marker Was Associated With Fluorouracil Resistance in Human Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most prevalent digestive tumors in China. Recent studies indicate that long intergenic non-coding RNAs (lincRNAs) play a crucial role in predicting survival for CRC patients. However, the novel lincRNA, LINC00957, is largely unclear in CRC. The purpose of the current study was to determine LINC00957 expression, assess its the clinical significance and explore the potential mechanism in CRC. The qRT-PCR was used to quantify the expression levels of LINC00957 in tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Identification of Prognostic EMT-Related lncRNA colorectal cancer patients (18); LINC02532 was demonstrated to act as an oncogene in gastric cancer (GC) and promoted the GC cell proliferation, migration, and invasion (19); DOCK9-DT was revealed to play a protective role in the prognosis of thyroid carcinoma (20); THUMPD3-AS1 regulated non-small cell lung cancer cell self-renewal via the expression of miR-543 and ONECUT2, and THUMPD3-AS1 can serve as a potential biomarker or therapeutic target in non-small cell lung cancer (21). Additionally, APCDD1L-DT exhibits a significant prognostic value in lung squamous cell carcinoma (LUSC) and can independently predict the overall survival in LUSC patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of Prognostic EMT-Related lncRNA colorectal cancer patients (18); LINC02532 was demonstrated to act as an oncogene in gastric cancer (GC) and promoted the GC cell proliferation, migration, and invasion (19); DOCK9-DT was revealed to play a protective role in the prognosis of thyroid carcinoma (20); THUMPD3-AS1 regulated non-small cell lung cancer cell self-renewal via the expression of miR-543 and ONECUT2, and THUMPD3-AS1 can serve as a potential biomarker or therapeutic target in non-small cell lung cancer (21). Additionally, APCDD1L-DT exhibits a significant prognostic value in lung squamous cell carcinoma (LUSC) and can independently predict the overall survival in LUSC patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…15 However, nearly 50% of colorectal cancer patients showed no response to 5-Fu, and more and more studies reported that fluorouracil resistance led to failure of CRC treatment. [16][17][18] But the mechanism is not clear. Therefore, biomarkers predicting the efficacy of fluorouracil are urgently needed in CRC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The long non-coding RNA00957 (LINC00957) was demonstrated to be involved in tumor progression, and Zhang et al [39] . found that the expression levels of LINC00957 were significantly associated with advanced TNM stage, poor chemotherapy outcomes, and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%